(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Co-curing is a manufacturing process where two or more composite parts are cured simultaneously in a single curing cycle. This creates a strong, integral bond between the components, eliminating the need for adhesives or mechanical fasteners. In this research, numerical analysis is conducted to investigate the damage mechanism of a glass fibre composite structure manufactured using co-curing techniques. This co-cured composite structure represents the core component of a hydrofoil, a wing-like device fitted to the bow of a ship. Hydrofoils are designed to improve the vessel’s performance in waves by reducing resistance and increasing stability. A four-point bending test is carried out to characterise the failure mechanism of the co-cured demonstrator. Test results revealed that the composite delamination, which occurred under a load of 123 kN, dominated the structure’s failure, indicating a high performance of the co-cured bonding. A detailed finite element model is generated using solid elements to predict the demonstrator’s structural performance. The model’s accuracy is verified against the test data. The detailed stress distribution development is extracted from the numerical analysis. The verified numerical model will be used to optimise a hydrofoil’s design in the future. Hydrofoil technology contributes to a greener environment by making ships more fuel-efficient and reducing their emissions. By reducing the ship’s fuel consumption, the harmful air pollutants and carbon dioxide, a major contributor to climate change, are decreased.